The Privacy-Driven Consumer: Reconceptualizing Online Purchase Intentions in the Digital Economy for Generation Z - Kiet, Le Quoc (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026DO - 10.14505/tpref.v17.2(38).07, 2026)
The rapid digital transformation has profoundly reshaped the global economic landscape, intensifying the exchange of personal data and raising significant privacy concerns within e-commerce. This study addressed the complex interplay between privacy attitudes and online purchasing behaviors among Generation Z, a digitally native cohort known for its paradoxical stance on data privacy. This study aimed to investigate how perceived privacy policies and privacy concerns influence online purchase intentions, thereby refining the theoretical understanding of the "privacy paradox" within the stimulus-organism-response framework. A quantitative cross-sectional survey was conducted to collect data from Generation Z online shoppers. Partial Least Squares Structural Equation Modeling was employed for data analysis, and the measurement and structural models were rigorously assessed for reliability and validity. The findings provide robust support for all hypothesized relationships. Specifically, perceived privacy policies positively influenced online purchase intentions and negatively impacted privacy concerns. Crucially, privacy concerns were found to positively influence online purchase intention. These results suggest that for Generation Z, privacy concerns act as a discerning filter, guiding their purchasing decisions towards trusted online platforms. The study concluded that transparent and effectively perceived privacy policies are strategic imperatives for e-commerce businesses to foster trust and drive engagement among this influential consumer demographic.